Stability Improvement Method for Multi-Converter Distribution Systems Based on Impedance Sensitivity - Yang Li; Zhikang Shuai; Junbin Fang; Xiangyang Wu (CSEE Journal of Power and Energy Systems)
This paper uses impedance sensitivity to identify the parameters that have dominant influences on the stability of multi-converter systems, which can then efficiently improve system stability. A modified 400 V IEEE 13-bus system with three converters is used as the study case, and a stability improvement method for multi-converter systems according to impedance sensitivity is introduced. Sensitivities of the real and imaginary parts of eigenvalues of the system's return-ratio matrix with respect to parameters (including control parameters and grid component parameters) are calculated at the cross-over frequencies, by which the parameters that have dominant influences on the system stability can be identified. Then, according to sensitivities, the system stability can be efficiently improved by adjusting the dominant parameters. Simulations in PSCAD/EMTDC and experiments of the control hardware in the loop validate the effectiveness of the proposed stability analysis method.